Composting as an Alternative to Waste Management at State University of Malang - Eli H. Sanjaya; Abdul K. Syahroni; Much S. Alwy; Mohamad F. Setyawan; Yudhi Utomo; Agung Witjoro; Mohd F. M. D. Din (Universitas Tadulako, 2024)
Waste is one factor that becomes an environmental problem. The waste that is often found is inorganic and organic. One of the uses of organic waste is the production of solid organic fertilizer in the form of compost. This research utilizes dried leaves (sono leaves, teak, trembesi, kenitu, breadfruit, and ketepeng) as raw materials for making compost. The compost-making method is carried out by adding an activator called EM4 (Effective Microorganism 4). This research produced pH values, Nitrogen, Phosphorus, Potassium, and Water Content per values under SNI 19-730-2004 regarding the specification of compost from organic waste. And the results of microbial diversity in the compost were obtained, which were dominated by microbes of the type Proteobacteria 40%, Firmicutes 30%, Actinobacteria 13%, Acidobacteria 6%, Bacteroidota 4%, Planctomycetota 3%.